Peningkatan Motivasi Petugas Kader Posyandu Dalam Memberikan Pelayanan Prima Di RW 06 Desa Susukan Bojong Gede - Ria Efkelin; Lipin Lipin; Imelda Imelda; Hingawati Setio; Ary Rahmaningsih; Ni Made Suarti (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
Motivation discusses how to encourage someone's work enthusiasm, so that they want to work by providing optimal abilities and expertise to achieve goals (Danang Sunyoto, 2015). Providing excellent service is an action that must be carried out by workers/service providers in serving the people or residents around them. If the service provider is not satisfactory, do not hope that the client will return to our services, he will switch to another health facility that provides excellent service. It cannot be denied that when we come to a health facility, even a type of Posyandu facility, sometimes we still find the health workers and cadres who work less friendly, less energetic in serving the people who come, seem less enthusiastic about the various factors that make them like that, with their attitude. health workers like this illustrate the lack of excellent service. By looking at conditions like this, the author is interested in providing/sharing knowledge related to how to increase the motivation of Posyandu cadre officers in providing excellent service in RW 06 Susukan Village